2021
DOI: 10.1002/cpp.2690
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of emotion‐focused therapy in the treatment of eating disorders: A systematic review

Abstract: Background The high incidence of eating disorders (EDs) means that its treatment is approached from various perspectives, among which we find emotion‐focused therapy (EFT). Therefore, the main objective of this systematic review was to know the effectiveness of EFT for eating disorders. Method A systematic review of PubMed, the Cochrane Library and the Psychology and Behavioural Sciences Collection was carried out without a time limit and in a population with an eating disorder diagnosis. Results Eight studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…In an effectiveness study comparing DBT and CBT in individuals diagnosed with BED, there were no significant differences in primary outcomes (global eating pathology and frequency of objective binge episodes) at follow‐up, indicating DBT's relevance in clinical practice as compared to CBT (Lammers et al., 2022). Furthermore, preliminary research has found other emotion focused treatments such as emotion‐focused therapy, acceptance and commitment therapy, and integrative cognitive‐affective therapy effective in reducing eating disorder pathology and behaviours in individuals with B‐ED's (Juarascio et al., 2013; Osoro et al., 2022; Wonderlich et al., 2014). Further investigating heterogeneity among established maintenance factors for eating disorders, such as emotion dysregulation, is essential.…”
Section: Introductionmentioning
confidence: 99%
“…In an effectiveness study comparing DBT and CBT in individuals diagnosed with BED, there were no significant differences in primary outcomes (global eating pathology and frequency of objective binge episodes) at follow‐up, indicating DBT's relevance in clinical practice as compared to CBT (Lammers et al., 2022). Furthermore, preliminary research has found other emotion focused treatments such as emotion‐focused therapy, acceptance and commitment therapy, and integrative cognitive‐affective therapy effective in reducing eating disorder pathology and behaviours in individuals with B‐ED's (Juarascio et al., 2013; Osoro et al., 2022; Wonderlich et al., 2014). Further investigating heterogeneity among established maintenance factors for eating disorders, such as emotion dysregulation, is essential.…”
Section: Introductionmentioning
confidence: 99%
“…There is, as mentioned, extant literature purporting a central role for emotion processing and regulation deficits in the ED spectrum [ 21 , 53 , 60 , 86 ], albeit in female samples, and these difficulties are hence addressed in psychological therapies for EDs. There is also preliminary support for the beneficial impact of emotion processing- and emotion regulation-focused interventions on ED symptomatology [ 80 , 87 ]. Against the backdrop of this literature, our findings support the perspective that emotion processing and regulation deficits are important in the aetiology of EDs.…”
Section: Discussionmentioning
confidence: 99%
“…The psychotherapist’s eclectic approach enabled her to draw upon strategies as indicated, primarily utilizing cognitive-behavioral, including third-wave approaches like Acceptance and Commitment Therapy (ACT) and Dialectical Behavior Therapy (DBT), humanistic, and psychodynamic therapies. Consistent with an evidence-based practice approach, these strategies were selected based on available research showing preliminary support for potential effectiveness with EDs (CBT, DBT, ACT: Muratore & Attia, 2021; humanistic: Osoro et al, 2022; psychodynamic: Abbate-Daga et al, 2016), the psychotherapist’s own expertise, and their fit with Gertrude’s presenting issues (see Table 2 for examples of how strategies were matched to treatment goals and objectives). The psychotherapist reported using psychodynamic interventions most often, documenting use for 96.88% of Gertrude’s sessions, followed by cognitive-behavioral (90.63%) and finally humanistic (84.38%).…”
Section: Course Of Treatment and Assessment Of Progressmentioning
confidence: 99%